2017
DOI: 10.1096/fj.201700407r
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania donovani inhibits inflammasome‐dependent macrophage activation by exploiting the negative regulatory proteins A20 and UCP2

Abstract: In visceral leishmaniasis, we found that the antileishmanial drug Amp B produces a higher level of IL-1β over the infected control. Moreover, administering anti-IL-1β antibody to infected Amp B-treated mice showed significantly less parasite clearance. Investigation revealed that inhibits stimuli-induced expression of a multiprotein signaling platform, NLRP3 inflammasome, which in turn inhibits caspase-1 activation mediated maturation of IL-1β from its pro form. Attenuation of NLRP3 and pro-IL-1β in infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 66 publications
(83 reference statements)
5
40
0
1
Order By: Relevance
“…Similarly, infection by L. donovani results in shutting down the production of IL‐1β at the transcription and translational level . Furthermore, small hairpin RNA‐mediated knockdown of either A20 or UCP2 in infected mice induced inflammasome‐mediated IL‐1β production and significantly decreased liver and spleen parasite burden, creating a host favourable anti‐leishmanial milieu . Consistent with this observation, the study by Shio et al also reported that expression of the metalloprotease GP63 is indispensable for Leishmania ‐mediated inhibition of NLRP3 inflammosome activation and dampening of IL‐1β secretion.…”
Section: Survival Strategy Of Leishmania Inside the Hostmentioning
confidence: 64%
See 4 more Smart Citations
“…Similarly, infection by L. donovani results in shutting down the production of IL‐1β at the transcription and translational level . Furthermore, small hairpin RNA‐mediated knockdown of either A20 or UCP2 in infected mice induced inflammasome‐mediated IL‐1β production and significantly decreased liver and spleen parasite burden, creating a host favourable anti‐leishmanial milieu . Consistent with this observation, the study by Shio et al also reported that expression of the metalloprotease GP63 is indispensable for Leishmania ‐mediated inhibition of NLRP3 inflammosome activation and dampening of IL‐1β secretion.…”
Section: Survival Strategy Of Leishmania Inside the Hostmentioning
confidence: 64%
“…Recently, a study on L. amazonensis demonstrated that ROS induced via NAD(P)H oxidase in macrophages during the early stages of L. amazonensis infection is critical for NLRP3 inflammasome activation . However, our work has documented that upon L. donovani infection, transcription of NLRP3 gets inhibited due to the upregulation of NF‐κB inhibitor A20 . Moreover, L. donovani simultaneously upregulates mitochondrial uncoupling protein‐2 (UCP2) , thereby inhibiting ROS production and ROS‐mediated pro‐IL‐1β processing .…”
Section: Survival Strategy Of Leishmania Inside the Hostmentioning
confidence: 79%
See 3 more Smart Citations